Laparoscopic Ureterolithotomy in Children: With and Without Stent — Initial Tertiary Care Center Experience with More Than 1-Year Follow-Up - Srivastava, Alok; Dhayal, Ishwar Ram; Rai, Priyanka (European Journal of Pediatric Surgery, 2017)
Background The purpose of our study was to assess the safety and feasibility of transperitoneal laparoscopic ureterolithotomy (LU) in children with ureteric stones with and without a stent.Method Impacted ureteric stone of size ≥ 1.5 cm or ureteric stones that were refractory to shock wave lithotripsy (SWL)/ureteroscopy (URS) were considered for LU. From December 2009 to April 2012, 50 cases of LU were performed with a stent being placed. From May 2012 onward we now perform stentless LU and till now we have done approximately 64 such type of cases. Out of these, 48 have completed more than 1 year of follow-up and we took these as our study group and the previous 50 (LU with stent) as our control group. Baseline characteristics along with certain per- and postoperative findings of the two groups were noted and analyzed. Ultrasonography and X-ray kidney, ureter, and bladder region were done at 3, 9 months, 1 year, and yearly thereafter. Intravenous urography was done at 6 months statistical analysis was performed by using SPSS ver. 21 (SPSS Inc., Chicago, Illinois, United States). The data were analyzed by using the Mann–Whitney test and a p value of < 0.05 was considered significant.Results The baseline characteristics were similar in both the groups with 100% stone clearance in all. LU with stent differed from the stentless group in terms of more requirement of analgesics and the need for a second procedure for stent removal, but with no cases of urine leak in the postoperative period.Conclusion LU in children is a safe and viable option, especially for impacted stones or as a salvage procedure for ureteric stones when SWL or transureteral lithotripsy has failed.
Keywords: children; stent; laparoscopic ureterolithotomy